Perlindungan Hukum terhadap Korban Perdagangan Orang dengan Modus Pekerja Migran Ilegal - Salsabila, Viyosi; Usman; Sudarti, Elly (Jurnal Alwatzikhoebillah : Kajian Islam, Pendidikan, Ekonomi, Humaniora, 2026)
Human trafficking conducted through the modus of illegal migrant workers remains a serious issue within the Indonesian legal system. In practice, migrant workers who are recruited and deployed through non-procedural mechanisms are often not recognized as victims of trafficking in persons, but instead are treated merely as administrative violators of labor and migration regulations. This approach results in inadequate legal protection for victims and undermines the effectiveness of criminal accountability for perpetrators. This research aims to analyze the regulation of legal protection for victims of trafficking in persons with the modus of illegal migrant workers and to examine criminal law policy in constructing the criminal responsibility of perpetrators. The research employs a normative juridical method using statutory and conceptual approaches. The findings indicate the existence of normative ambiguity and normative conflict between Law Number 18 of 2017 on the Protection of Indonesian Migrant Workers and Law Number 21 of 2007 on the Eradication of the Crime of Trafficking in Persons. These inconsistencies adversely affect the fulfillment of victims’ rights and weaken victim-oriented protection. Therefore, regulatory harmonization and a criminal law policy approach that prioritizes victim protection are necessary to ensure legal certainty and justice.